AETIOLOGY AND MANAGEMENT OF PRIMARY AMENORRHOEA - Abida Islam; Zubair, Maryam; Sami Wahid; Uzma Noreen (Journal of Ayub Medical College Abbottabad, 2021)
Background: Amenorrhoea is absence of menstruation. It could be primary, if menstruation has not occurred by the age of 16 years in the presence of normal growth and secondary sexual characters or by the age of 14 years in the absence of secondary sexual characters. It is secondary if periods have not occurred for six months. This study was done with the objective to determine the frequency of etiologic causes of primary amenorrhoea. Study Design: Cross-sectional descriptive study. Methods: The study was conducted in the department of Obstetrics and Gynaecology Sheikh Khalifha Bin Zyed Al Nahyan /Combined Military Hospital Muzaffarabad Azad Jammu Kashmir (SKBZ/CMH MZD AJK) from December 2014 to November 2017. Women with primary amenorrhoea reported and managed in the hospital are included in the study. Cases were analysed according to clinical profile, development of secondary sexual characteristics, physical examination, pelvic and rectal examination, hormonal profile, pelvic ultrasound, magnetic resonance imaging and cytogenetic study including karyotyping. Results: Three most common causes of primary amenorrhoea were Mullerian anomalies (36.7%) followed by gonadal dysgenesis (33.3%), hypothalamic causes (23.3%) and Pituitary causes (6.7%). There were 03 cases of polycystic ovarian syndrome and 02 cases of hyperprolactinemia. Conclusion: The most common etiological factor leading to primary amenorrhoea is Mullerian anomalies followed by gonadal dysgenesis. Genetic and environmental factors could also play role in the causes of primary amenorrhoea.